Can the Target Responsibility System of Air Pollution Control Achieve a Win-Win Situation of Pollution Reduction and Efficiency Enhancement? - Wang, Jie; Xu, Hao; Xu, Jingxuan (Frontiers in Energy Research, 2022)
Whether the environmental target responsibility system, a typical mandatory environmental regulation, can realize the coordinated development of environmental protection and economic growth has attracted widespread attention. With the difference-in-differences (DID) method, this paper utilizes a policy, “China’s Key Cities for Air Pollution Control to Meet the Standards within the Time Limit (APCMS),” as a quasi-natural experiment to empirically examine the target responsibility system of air pollution control’s effect on both firms’ pollutant emissions and their total factor productivity (TFP). The corresponding mechanisms are also investigated. The results show: 1) The policy not only significantly decreases firms’ pollutant emissions, but also improves their TFP. The results are robust to the exclusion of the impact of other policies in the same period, propensity score matching DID (PSM-DID) test, the adoption of alternative dependent variables, and altering sample interval; 2) The dynamic analysis shows that the policy effect on reducing pollutant emissions has increased over years after a lag of 2 years; 3) The policy reduces pollutant emissions mainly through stimulating the internal innovation rather than end-pipe treatment or production cuts. 4) Capital-intensive and private firms and firms in regions with a high degree of marketization or strong environmental law enforcement are found more responsive to the environmental target responsibility system.